UPAYA GREENPEACE MENYELAMATKAN ARKTIK DARI KEPENTINGAN PENGEBORAN MINYAK DAN GAS RUSIA - Zuhdi, Andri; Fachri, Yuli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to find out about the Greenpeace efforts in save the arctic from interestd oil and gas drilling russia. Type of this research is descriptive analysis. The decades of the environment is a new issue and the most hotly discussed issues in the international world. Global warming and climate change has threatened the world for causing extreme changes in weather to natural disasters. Earth's polar axis and has an important function for the earth. Behind the threats, the Arctic have a source of potential oil and gas reserves of the world. Russia became a very ambitious country on this potential, to issue a policy to get this potential by drilling for oil and gas in the Arctic through the international oil and gas company's russia. Greenpeace is one of the largest NGO in the world and a vision for the environment, issued a petition rejection of oil drilling in the Arctic or the north pole undertaken by the Russian oil company because impact of global warming and climate change.The writer try to describe and explain about Greenpeace efforts to save the arctic region from the Russian oil and gas drilling and its impact on the environment in the Arctic ecosystem good nor bad in the world. Sources that will be presented in this study is a secondary source. The conclusion of this research effort conducted by Greenpeace to save the Arctic from oil and gas drilling russian, useful to stop them and make the arctic region to be protects.Keywords: greenpeace, efforts, arctic, russian oil and gas drilling.